THE IMPACT OF COMPETENCY AND WORK PLACEMENT ON EMPLOYEE PERFORMANCE AT THE TOURISM OFFICE OF SLEMAN REGENCY - Septianisa, Septianisa; Khozin, Muhammad (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Increased competition motivates organizations to continue enhancing performance. Transferring and promoting employees is one measure that can be taken to enhance employee performance. The mutation is anticipated to serve as the appropriate link between employees and positions. The purpose of this study is to investigate the mechanism of employee placement and the requisite competencies at Sleman Regency Tourism Office, as well as the effect of competence and job placement on employee performance. This study employed diverse research methodologies (Mixed Method). The sample in this study was 59 civil servants, freelance daily workers, and freelancer workers at Sleman Regency Tourism Office, which was determined by using the disproportionate stratified random sampling technique. The instrument utilized in this investigation is subjected to validity and reliability testing. Data collected using a questionnaire, interview, and documentation. The analysis was performed by data reduction, triangulation, drawing conclusions, multiple linear regression, and hypothesis testing. The study findings indicate that partial competence has a positive and significant impact on employee performance. The work environment has a significant and positive effect on employee performance. This is also supported by the findings of interviews, which indicate that the quality of employee performance will increase if the work placement is conducted properly and appropriately. This study demonstrates that both competence and work placement have a significant impact on performance. The R value for all Sleman Regency Tourism Office employees with a coefficient of determination is 0.500, or 50.0%.